Effect of Employing Micro-Learning in an E-learning Environment on Correcting Spelling Errors Among Middle School Students - Al-Shaibani, AlJawhara Naif; Ismail, Abdellraouf Mohamed Mohamed (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to identify the most common spelling mistakes among the intermediate first-grade, and to develop the educational content model in employing micro-learning. the researcher used the quasi-experimental approach and an achievement test to measure the cognitive aspects related to correcting spelling mistakes in the Arabic language course as a tool. the study sample consisted of 40 female intermediate first grade students who were randomly selected and divided into two groups: a control group (15 students) and an experimental group (15 students), after choosing the exploratory group (10 students). the study reached a set of results, the most important of which were: there are statistically significant differences in favor of the experimental group at (α
Keywords: Micro-Learning; E-learning Environment; Correcting Spelling Errors